The mediating role of technology acceptance and moderating role of emotion regulation in faculty’s online professional development - Lin, Xiaochen; Wang, Qian; Limniou, Maria; Huijser, Henk; Yu, Jeong Jin; Gu, Haibo (Australasian Journal of Educational Technology, 2024)
Higher education faculty members have different attitudes about taking professional training courses online despite the post-pandemic shift towards e-learning. Limited studies have linked faculty’s emotions with their acceptance of technology and investigated their impacts on learning engagement in online professional development. This study addresses this gap by testing the mediating effect of technology acceptance between learning-related emotions and online learning engagement in professional development and the moderating effect of emotion regulations therein. The study is theoretically grounded in control-value theory, unified theory of acceptance and use of technology, alongside the process model of emotion regulation. After collecting data from 254 higher education faculty members (146 females) through an online questionnaire, the study applied a partial least squares structural equation model for its results. The findings show that learning-related emotions are associated with technology acceptance, while emotion regulation plays a moderating role. The results further show that technology acceptance mediates between learning-related emotions and online learning engagement. The findings identify a need to attend to faculty’s emotional dimensions in online learning and stress the importance of emotionally embracing technology in learning engagement among faculty. Implications for practice or policy: Instructors should provide appropriate emotional support to faculty. Designers should include pre-sessional courses in the curriculum to introduce the value and ease of using learning technologies. Higher education institutions should offer training to enhance faculty’s abilities to regulate their emotions. Higher education institutions should provide accessible, stable and reliable learning technologies along with an inclusive and supportive culture for online professional development.